1974
DOI: 10.1161/01.cir.49.6.1053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Digoxin Level Measurement with Acetyl Strophanthidin Tolerance Testing

Abstract: SUMMARYSerum digoxin levels (SDL) were compared with tolerance for the rapidly acting cardiac aglycone, acetyl strophanthidin (AS). AS titration tests were performed on 133 patients with diverse cardiac disorders. All were receiving maintenance digoxin. Both exquisite AS sensitivity and tolerance for a 1.0 mg AS were associated with a wide range of SDL values. Concordance and discordance between the two methods in assessing degree of digitalization were evaluated by considering SDL of 1.4 ng/ml to be the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…There was no age difference in the extent of inhibition expressed as a percent of total inhibition over the entire range of concentrations of the glycoside. Discussion VT, as an index of toxicity, has been used previously and the range of ACS concentrations over which VT occurred is similar in this study to that reported for other adult dogs.4 23 There was no difference in the threshold for ACS toxicity, defined as VT, in the senescent dogs compared with the adult dogs (table 1).…”
Section: Na+-k+ Atpase Inhibitionsupporting
confidence: 85%
“…There was no age difference in the extent of inhibition expressed as a percent of total inhibition over the entire range of concentrations of the glycoside. Discussion VT, as an index of toxicity, has been used previously and the range of ACS concentrations over which VT occurred is similar in this study to that reported for other adult dogs.4 23 There was no difference in the threshold for ACS toxicity, defined as VT, in the senescent dogs compared with the adult dogs (table 1).…”
Section: Na+-k+ Atpase Inhibitionsupporting
confidence: 85%
“…Therefore, while in one patient a low serum level may be an adequate indication of the control of heart failure, in another patient a higher level, sometimes in the toxic range, may be necessary. Klein and co‐workers (5) demonstrated this situation with the acetylestrophanthidin test performed in patients receiving a maintenance dose of digoxin. They showed that in 22 percent of patients with a serum digoxin level of less than 0.7 ng/ml, arrhythmia was induced by less than 0.6 mg of acetylstrophanthidin, indicating that the patients were exquisitely sensitive to digoxin.…”
Section: Discussionmentioning
confidence: 91%
“…This overlap is most marked in prospective blinded studies, and has led some investigators to question whether knowledge of serum digoxin concentrations really enhances clinical decision-making beyond routinely available data such as renal function and body mass (Ingelfinger and Goldman, 1976). Klein et al (1974) used the rapidly acting cardiac aglycone acetyl-strophanthidin in digitalised patients to assess their ability to tolerate more digitalis. They found in 42% of cases that the digoxin concentration alone did not predict the response to incremental digitalis doses.…”
Section: Relationship Between Serum Concentration and Therapeutic Effectmentioning
confidence: 99%
“…They found in 42% of cases that the digoxin concentration alone did not predict the response to incremental digitalis doses. Thus, many patients with serum digoxin concentrations greater than 2.0 ng/ml could tolerate more digitalis without toxicity, while others with concentrations in the 0.5 to 1.5 ng/ml range were either close to or already showing toxicity (Klein et al, 1974).…”
Section: Relationship Between Serum Concentration and Therapeutic Effectmentioning
confidence: 99%